Debating Uneven and Combined Development/Debating International Relations: A Forum. (January 2022) - Rosenberg, Justin; Zarakol, Ayşe; Blagden, David; Rutazibwa, Olivia; Gray, Kevin; Corry, Olaf; Matin, Kamran; Antunes de Oliveira, Felipe; Cooper, Luke
This forum arises from an online event on the theory of uneven and combined development (UCD). Following an introduction which proposes a 'special affinity' between UCD and International Relations (IR), four presenters at that event discuss their 'view from outside' UCD, including perspectives from Global Historical Sociology, Realism, Decolonial theory and Gramscian Marxism. Meanwhile four members of the audience add their views on UCD and disciplinarity, the need for pluralism in UCD methodology, UCD and 'whiteness', and its potential contribution to ecological theory and practice. Débattre du développement inégal et combiné/Débattre des relations internationales